Research of caspase-dependent mechanisms of apoptosis induction and the activity of peroxidation and antioxidant defense in the thyroid tissue of patients with nodular forms of goiter combined with autoimmune thyroiditis and thyroid adenoma depending on the allelic status of Bcl-2 (rs17759659), CTLA-4 (rs231775), APO-1 / Fas (rs2234767) genes - Sheremet, M. I. (Journal of Education, Health and Sport, 2017)
The aim of the work is to analyze the mechanisms of caspase-dependent apoptosis and pro- and antioxidant activity in the thyroid tissue homogenate in patients with in patients with nodular goiter with autoimmune thyroiditis and thyroid adenoma considering the polymorphic variants of BCL-2 (rs17759659), CTLA-4 (rs231775), APO-1 / Fas (rs2234767) genes. Methods of research: We investigated pro- and antioxidant activity and the activity of caspases 3 and 8in 5% of thyroid tissue homogenates. The BCL-2 (rs17759659), CTLA-4 (rs231775), Fas (rs2234767) genes polymorphism were studied by Real-Time Polymerase Chain Reaction in 95 patients with nodular goiter on the background of autoimmune thyroiditis, 30 patients with thyroid adenoma and 25 healthy individuals. Results: We have not found any pronounced dependence of the processes oxidative modification of proteins and antioxidant protection nor the activity of caspasess-8 and3 in the thyroid tissue on the genotypes of BCL-2 (rs17759659) and APO-1/Fas (rs2234767) genes. However, it should be noted that in homozygous carriers of A-allele of the BCL-2 (rs17759659) gene the activity of effector caspase-3 is higher than that in the control group. The imbalance between the activity of peroxidation and antioxidant defense in patients with nodular goiter on the background of autoimmune thyroiditis and thyroid adenoma is associated with the promoter of the CTLA-4 (rs231775) and APO-1 / Fas (rs2234767) genes and is characterized by an increasing degree of oxidative modification of proteins in the altered thyroid tissue alongside with a lower capacity of the antioxidant protection system enzymes.